Is traditional marketing mix still suitable for hotel banquets? An empirical study of banquet marketing in five-star hotels - Yin, Jie; Fang, Sha; Cheng, Yun (Frontiers in Psychology, 2022)
Are traditional marketing mix strategies still fit for hotel banquet marketing? This study used 763 banquet sales records in Quanzhou Hilton Hotel to comprehensively test the influence of traditional marketing mix strategies on the banquet marketing effects using the binary logistic regression analysis method. By focusing on new forms of marketing methods (such as video, Internet, and WeChat marketing), this study tested the effectiveness of traditional marketing strategies in the era of new media. The findings revealed that a combination of products is easier to market than a single product, whereas the price is still a key factor in hotel banquet marketing. However, sales channels and personal identity have no significant effects on banquet marketing. Finally, based on the failure cases analysis, the study proposed a feasible path for promoting banquet marketing.